Academic writing with corpora : a resource book for data-driven learning - Karpenko-Seccombe, Tatyana (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Academic Writing with Corpora offers a step-by-step accessible guide to using concordancers and aims to help introduce data-driven learning into the academic English classroom. Addressing the challenges faced by EAP teachers to explain to their students how to write "naturally", this book provides a solution to the problem by placing an emphasis on learning from expert and proficient writing. In doing so, it: takes a highly practical approach and is packed with pedagogical features including graded tasks; uses Lextutor, an easy-to-use, open access concordancer, throughout, whilst introducing students to tools such as SkELL, MICUSP and BNC BYU; fosters autonomous learning by demonstrating how to solve everyday difficulties in word choice and grammar; helps teachers to use concordancers to teach students how to write proficiently and helps students to improve their academic writing by learning from best examples in their field. Showing students how to solve for themselves everyday difficulties in word choice and grammar, Academic Writing with Corpora will guide them towards better awareness of the communicative side of academic writing. It forms essential reading for all students on academic writing and EAP courses or who wish to improve their writing"--
Introduction to corpus tools -- Observing and using language patterns -- Using corpora to write for different academic purposes -- Writing research papers with corpora.
OCLC-licensed vendor bibliographic record.
Keywords: Academic writing -- Study and teaching (Higher); Academic language -- Study and teaching (Higher); Academic language -- Research -- Methodology; English language -- Study and teaching -- Foreign speakers; English language -- Research -- Methodology; Corpora (Linguistics) -- Databases; Concordances -- Databases; Second language acquisition; LANGUAGE ARTS & DISCIPLINES / Linguistics